Prevalence, correlates, and trends of intimate partner violence against women in Sierra Leone: findings from 2013 and 2019 demographic and health surveys - Masood Ali Shaikh (Frontiers Media S.A., 2023)
BackgroundIntimate partner violence (IPV) is a globally pervasive public health and medical problem in addition to being a serious violation of women's rights. The two-fold objectives of this study were to compute the lifetime prevalence and correlates of IPV perpetrated by current/former husbands/partners of ever-married women aged 15-49 years using the nationally representative Sierra Leone Demographic and Health Survey (DHS) conducted in 2019; ethnicity-based levels and trends of IPV were also computed using the data from the DHS conducted in 2013 along with the 2019 DHS.MethodsTwelve IPV correlates pertaining to socio-demographic, attitudinal, and experiential attributes were analyzed using logistic regression models for bivariate and multivariable analysis. IPV was computed as a composite variable comprising of physical, emotional, and/or sexual IPV.ResultsLifetime prevalence of experiencing any kind of IPV was a staggering 60.81%, whereas emotional, physical, and sexual IPV prevalence were reported by 45.90%, 49.81%, and 8.14% of the respondents, respectively. No ethnicity reported a statistically significant decrease in any type of IPV during the intervening period between the two surveys. Five out of nine ethnicities reported a statistically significant increase in emotional IPV, while few ethnicities reported a statistically significant increase in one or more types of IPV.ConclusionThe high lifetime prevalence of IPV is alarming and points to the need for targeted health promotion campaigns to reverse the tide of IPV in Sierra Leone, including focusing on changes in cultural and ethnicity-based norms and mores to ensure women's human rights are respected and upheld.